Seasonal changes of immunocompetence and parasitism in chub (Leuciscus cephalus), a freshwater cyprinid fish - Lamková, Karolína; Simková, Andrea; Palíková, Miroslava; Jurajda, Pavel; Lojek, Antonín (Parasitology research, 2007)
Seasonal variation of water characteristics, predominantly temperature, is considered to strongly affect fish physiology and immunology. In nature, this variation directly influences the life cycle especially in fish parasites, but the infection of parasites is also altered by the host immune response. This study is aimed to analyze the seasonal changes in selected physiological and immunological parameters, the latter a potential measure of fish immunocompetence. Moreover, the seasonal changes in metazoan parasite infection were investigated, and the potential associations between fish physiology, immunocompetence, and parasitism were estimated. No differences in gender were recognized for immunological parameters. The significant differences in the spleen-somatic index were found among fish samples of different seasons indicating higher investment in spleen size in April (after winterizing) and August (post-breeding with low gonado-somatic index [GSI]). The significant seasonal differences in erythrocyte and leukocyte cell counts, as well as in phagocyte count affecting respiratory burst, were recorded. The general trend of leukocyte composition was similar in all seasons investigated; however, the changes in proportion of different neutrophilic cells were reported. The parasite diversity and the infection parameters in parasite communities were highest in spring and early summer. When comparing parasite abundance in infracommunities among seasons, the statistically highest values were observed in April and June for Monogenea, in April and November for Acanthocephala, and in April for Cestoda. The positive correlations between GSI and the parasite abundance of groups with higher infection parameters were found in males. Moreover, the positive association between Monogenea as the dominant parasite group and respiratory burst was observed. The higher investment in condition and the seasonal variation in GSI were associated with a decrease immune function measured by spleen size or leukocyte cell count especially for males suggesting the seasonal energy allocation between immune function and somatic or reproductive investment.
Keywords: sladká voda; Leeches; Male; roční období; měkkýši; Seasons; Host-Parasite Interactions; Fish Diseases; interakce hostitele a parazita; nemoci ryb; Animals; Helminths; helmintózy zvířat; zvířata; pijavice; Fresh Water; mužské pohlaví; cizopasní červi; Parasitic Diseases, Animal; parazitární nemoci u zvířat; Helminthiasis, Animal; Cyprinidae; Mollusca; ženské pohlaví; Female